Elevated Risk of HPV-Associated Oropharyngeal Cancers in Husbands of Women With Anogenital Cancer - Lehtinen, Tuomas; Zhang, Luayo; Sundquist, Kristina; Sundquist, Jan; Waterboer, Tim; Lehtinen, Matti; Hemminki, Kari (Cancer Reports, 2025)
Introduction: Human papillomavirus (HPV) infection is associated with tonsillar and base-of-tongue squamous cell carcinomas (TSCC/BOTSCC). We evaluated the relative risk (RR) of TSCC/BOTSCC in the husbands of women with anogenital cancer using the Swedish family database. Methods: The Swedish family database includes 3.5 million families and 16 million individuals identified since 1932 and linked to cancer data from 1958 to 2015. We explored the RR of TSCC/BOTSCC in husbands of women diagnosed with anogenital (anal, vulvar/vaginal, cervical) cancer or cervical carcinoma in situ (CIS) as compared to husbands of controls. Results: The RR of TSCC/BOTSCC in husbands of women with invasive anogenital cancer increased by calendar time and decreasing ages at diagnoses. In 2002–2015, the RR peaked at 5.35 (95% CI 2.21–13.0) in TSCC/BOTSCC cases diagnosed at age < 50 years. In husbands of women with CIS, the RR for TSCC/BOTSCC was 2-fold irrespective of time period. Conclusions: Clustering of increased HPV-associated invasive cancer risk in spouses appears to be calendar-time dependent. This introduces a new perspective in cancer science: an increase of familial HPV-associated cancer risk in spouses.
Keywords: familial cancer; head and neck cancer; viral infection; viral oncology